Exploring determinants shaping recycling behavior using an extended theory of planned behavior model: An empirical study of households in Sabah, Malaysia - Natasha Juliana; Suddin Lada; Brahim Chekima; Azaze @ Azizi Abdul Adis (Multidisciplinary Digital Publishing Institute (MDPI), 2022)
Household waste and the exploitation of the environment are among the alarming and unsustainable consumption patterns that are harmful to the ecosystem. Hence, this study aims to determine the factors influencing recycling behavior by extending the theory of planned behavior (TPB) to an analysis of how recycling practices are fostered among citizens and how sustainable development goals (SDG) are upheld. The extended TPB model includes moral norms, convenience, and the cost of recycling. A total of 170 responses were received via the purposive sampling technique. The research model was analyzed using the partial least square structural equation modeling technique (PLS-SEM). Results show that subjective norms, moral norms, convenience, and the cost to recycle positively influenced recycling behavior. Environmental awareness was found to heavily influence attitudes, but attitudes were not found to translate into behavior. This research provides significant insight and a better understanding of recycling behavior and adds new momentum to the growing literature. The implications of these findings are further discussed.